A composite lyophilized powder for injection and a method for preparing the same
Patent Information
- Application Number
- CN202611314227.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-11-03
AI Technical Summary
Traditional hyaluronic acid injections degrade quickly, resulting in short-lasting effects. Polylactic acid microsphere injections are difficult to re-dissolve and prone to needle clogging. The carrier material CMC can cause inflammation, making it impossible to achieve a comprehensive effect.
Small-particle-size poly(L-lactic acid) microspheres were compounded with sodium hyaluronate and mannitol, and phosphate was added. The lyophilized powder was prepared by microfluidic technology, and the particle size and resolubility were controlled by the lyophilization process.
It achieves short reconstitution time and low viscosity, making it easy to inject, reducing pain, providing immediate hydration and long-term moisturizing effects, while stimulating collagen regeneration and improving skin condition.
Smart Images

Figure CN123024005A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical materials technology, specifically to an injectable composite lyophilized powder and its preparation method. Background Technology
[0002] Hyaluronic acid is an acidic mucopolysaccharide widely found in human connective tissue. It is as clear and transparent as glass, hence its other name, hyaluronic acid. Hyaluronic acid has high hydrophilicity and is a natural moisturizing factor in the body, thus it is widely used in cosmetics, food, and medical devices. However, because the human body also contains hyaluronidase, the highly fluid hyaluronic acid is rapidly degraded after injection, leading to the common problem of rapid degradation and short-lasting effects in traditional mesotherapy. To address this issue, cross-linking methods are often used to form high-viscosity sodium hyaluronate gel, slowing down its degradation and absorption in the body. However, with increasing cross-linking, the granular feel of hyaluronic acid and the inflammatory response gradually increase, and most cross-linking agents used are toxic, further increasing safety risks. In addition, other ingredients can be added to the sodium hyaluronate gel to prolong its effects.
[0003] Poly-L-lactic acid (PLLA) is a biodegradable polymer. In the human body, it degrades into L-lactic acid, a natural substance that can be further metabolized into carbon dioxide and water and completely excreted. It was initially used in absorbable sutures. In recent years, scientists have discovered that it can stimulate collagen regeneration in the skin through a dual mechanism of physical stimulation and biological signal activation. Furthermore, with ongoing research, medical researchers have observed significant differences in the distribution, degradation rate, bodily response, and improvement effects of PLLA microspheres of different particle sizes in the human body. Small-particle-size PLLA microspheres (20-40 μm) offer better injection safety, slower sedimentation after reconstitution, are less prone to clumping, and can quickly improve skin condition.
[0004] However, traditional polylactic acid (PLA) microsphere injection products suffer from poor hydrophilicity, making them difficult to re-dissolve. Furthermore, re-dissolved PLA microspheres tend to aggregate and deposit, causing needle clogging during intradermal injection. Most existing products on the market use sodium carboxymethyl cellulose (CMC) as a carrier to mitigate these drawbacks. However, CMC is not an endogenous substance in the human body and can easily cause foreign body reactions, leading to inflammation. In addition, CMC only provides physical support and cannot provide additional biological activity, failing to achieve a synergistic effect. Summary of the Invention
[0005] The purpose of this invention is to provide an injectable composite lyophilized powder and its preparation method, thereby solving the above-mentioned problems.
[0006] In order to achieve these objectives and other advantages according to the present invention: In one aspect, an injectable composite lyophilized powder comprises poly-L-lactic acid microspheres, sodium hyaluronate, and mannitol.
[0007] Furthermore, the poly-L-lactic acid microspheres, sodium hyaluronate, and mannitol are in a mass ratio of (3-4):(0.5-1.5):(2-4), with the remainder being phosphate.
[0008] Furthermore, the molecular weight of the sodium hyaluronate is 200-800 kDa.
[0009] Furthermore, the poly-L-lactic acid microspheres have a particle size of 20-40 μm.
[0010] Furthermore, phosphates are added, which are one or both of sodium dihydrogen phosphate and disodium hydrogen phosphate.
[0011] Secondly, a method for preparing a compound lyophilized powder for injection includes the following steps: S1: Preparation of poly-L-lactic acid microspheres; S2: Preparation of excipient solution: Add sodium hyaluronate, mannitol, and phosphate to water for injection and stir to dissolve; S3: Add the prepared poly-L-lactic acid microspheres to the excipient solution and stir to mix well; S4: Freeze-dry to obtain a composite lyophilized powder for injection.
[0012] Furthermore, in step S1, the preparation of poly-L-lactic acid microspheres includes: S101: Polyvinyl alcohol is mixed and dissolved with water for injection to obtain an aqueous phase; dichloromethane and poly-L-lactic acid are mixed and dissolved to obtain an oil phase; S102: The oil phase and aqueous phase solutions are filtered through a 0.22um filter membrane and connected to the designated channels of the microfluidic chip. The flow rate of the two phases is controlled by the negative pressure of the air pump, so that stable microspheres with a particle size of 20-40um can be continuously formed. S103: The obtained microspheres are cured and the organic solvent is removed by evaporation. The polyvinyl alcohol is washed away by repeated water washing. After collection and drying, poly-L-lactic acid microspheres are obtained.
[0013] Furthermore, the phosphate includes sodium dihydrogen phosphate and disodium hydrogen phosphate.
[0014] Furthermore, in step S4, the freeze-drying step includes: S401: Pre-freeze the solution obtained in step S3 at -45°C for 2-3 hours; S402: Single drying: Maintain at -20℃ to -25℃ for 48 to 52 hours; S403: Secondary drying: Maintain at 10℃~30℃ for 10~15 hours to complete.
[0015] The beneficial effects of this invention are: 1. The injectable composite lyophilized powder of the present invention combines sodium hyaluronate and small-particle-size polylactic acid microspheres, resulting in a lyophilized powder with a short reconstitution time and low viscosity after reconstitution, which facilitates injection.
[0016] 2. The injectable compound lyophilized powder of the present invention, after being reconstituted with sterile water, has an osmotic pressure close to the normal osmotic pressure of the human dermis, reducing injection pain and improving the injection experience.
[0017] 3. The preparation method of the polylactic acid composite lyophilized powder for injection described in this invention uses poly-L-lactic acid microspheres prepared by microfluidic technology. The operation steps are simple, the particle size is uniformly controlled, and the needle penetration is good.
[0018] 4. The polylactic acid composite lyophilized powder for injection described in this invention can be used for cosmetic injections. After reconstitution, it can be injected into the dermis to provide immediate hydration, deep moisturization, and brighten skin tone. At the same time, it can also stimulate collagen regeneration, improve facial fine lines, and provide both immediate and long-term effects.
[0019] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Attached Figure Description
[0020] Figure 1 A microscope image of the poly-L-lactic acid microspheres prepared in Example 1, magnified 40 times; Figure 2 Here is a photograph of the composite lyophilized powder prepared in Example 1; Figure 3 A photograph of the composite lyophilized powder prepared in Example 1 after reconstitution and uniform dispersion. Figure 4 The image shows the appearance of the composite lyophilized powder prepared in Example 1 after reconstitution and standing for 20 minutes. Figure 5 The table below shows the physicochemical test data of the composition in Experiment Example 1; Figure 6 The results of the resolution and sedimentation time tests for Experiment Example 2; Figure 7 The results of the pushing test in Experiment Example 3; Figure 8 The results of the cell experiments in Experiment Example 4 are shown. Detailed Implementation
[0021] The present invention will now be described in further detail with reference to the accompanying drawings, so that those skilled in the art can implement it based on the description.
[0022] Exemplary embodiments will now be described in detail, examples of which are illustrated in the accompanying drawings. When the following description relates to the drawings, unless otherwise indicated, the same numerals in different drawings denote the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with this specification. Rather, they are merely examples of apparatuses and methods consistent with some aspects of this specification as detailed in the appended claims.
[0023] The terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to be limiting of this specification. The singular forms “a,” “the,” and “the” as used in this specification and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise. It should also be understood that the term “and / or” as used herein refers to and includes any and all possible combinations of one or more of the associated listed items.
[0024] It should be understood that although the terms first, second, third, etc., may be used in this specification to describe various information, this information should not be limited to these terms. These terms are only used to distinguish information of the same type from one another. For example, without departing from the scope of this specification, first information may also be referred to as second information, and similarly, second information may also be referred to as first information. Depending on the context, the word "if" as used herein may be interpreted as "when," "when," or "in response to determination."
[0025] The problem-solving approach of this invention:
[0026] An injectable composite lyophilized powder comprises sodium hyaluronate (molecular weight 200-800 kDa), poly-L-lactic acid microspheres (microsphere particle size 20-40 μm), mannitol, and phosphates (sodium dihydrogen phosphate, disodium hydrogen phosphate). The mass ratio of poly-L-lactic acid microspheres, sodium hyaluronate, and mannitol is (3-4):(0.5-1.5):(2-4), with the remainder being phosphates.
[0027] The specific preparation method is as follows: (1) Preparation of small-particle-size poly(L-lactic acid) microspheres: Polyvinyl alcohol was mixed and dissolved with injection water (80℃±2℃) to obtain an aqueous phase; dichloromethane and poly(L-lactic acid) were mixed and dissolved to obtain an oil phase. The oil and aqueous phase solutions were filtered through a 0.22µm filter membrane and connected to designated channels of a microfluidic chip. The flow rates of the two phases were controlled by the negative pressure of an air pump to ensure the continuous formation of stable microspheres. The obtained microspheres were subjected to evaporation to remove organic solvents and repeated washing with water to remove polyvinyl alcohol. After collection and drying, small-particle-size poly(L-lactic acid) microspheres with a particle size of 20-40µm were obtained. The microscope image after 40x magnification is shown below. Figure 1 .
[0028] (2) Preparation of excipient solution: Sodium hyaluronate, mannitol, sodium dihydrogen phosphate, and disodium hydrogen phosphate are added to water for injection. In a 100 mL solution system, the content of sodium hyaluronate is 1 g (molecular weight 500 kDa); the content of mannitol is 3 g; the content of disodium hydrogen phosphate is 465 mg; and the content of sodium dihydrogen phosphate is 255 mg. The solution is stirred and dissolved, and then filtered through a 0.22 μm filter membrane for sterilization.
[0029] (3) Add the prepared small-particle-size poly(L-lactic acid) microspheres to the above-mentioned excipient solution and stir to mix evenly. The mass ratio of poly(L-lactic acid) microspheres, sodium hyaluronate and mannitol is 4:1:3.2.
[0030] (4) Preparation of compound lyophilized powder for injection: The prepared solution was filled into vials with a filling amount of 5.0±0.15g and then freeze-dried. The freeze-drying parameters included: pre-freezing at -45℃ for 2-3 hours; primary drying at -20℃ to -25℃ for 48-52 hours; secondary drying at 10℃ to 30℃ for 10-15 hours. The drying was then completed. The actual product photo is shown below. Figure 2 .
[0031] Example 2-3 The difference between Examples 2-3 and Example 1 is the content of sodium hyaluronate; all other reaction conditions are the same as in Example 1. In Example 2, the mass ratio of poly(L-lactic acid) microspheres, sodium hyaluronate, and mannitol is 4:0.5:3.2. In Example 3, the mass ratio of poly(L-lactic acid) microspheres, sodium hyaluronate, and mannitol is 4:1.5:3.2.
[0032] Examples 4-5 The difference between Examples 4 and 5 and Example 1 is that the molecular weight of the sodium hyaluronate is different, while all other reaction conditions are the same as in Example 1. In Example 4, the molecular weight of the sodium hyaluronate is 200 kDa; in Example 5, the molecular weight of the sodium hyaluronate is 800 kDa.
[0033] Examples 6-7 The difference between Examples 6 and 7 and Example 1 lies in the content of the small-particle-size poly-L-lactic acid microspheres; all other reaction conditions are the same as in Example 1. In Example 6, the mass ratio of poly-L-lactic acid microspheres, sodium hyaluronate, and mannitol is 3:1:3.2. In Example 7, the mass ratio of poly-L-lactic acid microspheres, sodium hyaluronate, and mannitol is 3.5:1:3.2.
[0034] Examples 8-9 The difference between Examples 8-9 and Example 1 is the content of mannitol; all other reaction conditions are the same as in Example 1. In Example 8, the mass ratio of poly(L-lactic acid) microspheres, sodium hyaluronate, and mannitol is 4:1:2. In Example 9, the mass ratio of poly(L-lactic acid) microspheres, sodium hyaluronate, and mannitol is 4:1:4.
[0035] Experimental Example 1 Physicochemical tests were performed on the above Examples 1-9. The prepared composite lyophilized powder was reconstituted with 5 mL of sterile water (e.g., Figure 3 This is a photograph of the product after reconstitution and uniform dispersion, as shown in Example 1. Figure 4 The image shown is a photograph of the appearance after reconstitution and standing for 20 minutes in Example 1. The pH and osmotic pressure were measured according to the Chinese Pharmacopoeia (2025 edition), and the results are shown below. Figure 5 Table in Chinese.
[0036] The results showed that the pH of Examples 1-9 was neutral. The osmotic pressure of Examples 1-7 was close to the normal osmotic pressure of the human dermis (260-320 mOsm / kg), while the osmotic pressure of Example 8 was lower and that of Example 9 was higher. Non-isotonic solutions are prone to causing severe pain during injection, leading to abnormal redness and swelling after injection, and in severe cases, tissue damage. Therefore, Examples 1-7 are more suitable for facial injection, reducing the stinging sensation and adverse reactions caused by hypertonic or hypotonic injections. Examples 1-7 were preferred for further testing.
[0037] Experiment Example 2 Reconstitution time and sedimentation time were tested for Examples 1-7 above. The prepared composite lyophilized powder was reconstituted with 5 mL of sterile water, and manually shaken until completely dissolved. The time required for dissolution was recorded, and then the sedimentation time of the microspheres was observed by standing. The test results are shown in […]. Figure 6 Table in Chinese.
[0038] The results showed that, except for Examples 3 and 5, all other examples achieved complete reconstitution within 5 minutes. Except for Examples 2 and 4, the settling time for all other examples was more than 15 minutes.
[0039] Experimental Example 3 Push tests were conducted on Examples 1-7 above. The prepared composite lyophilized powder was reconstituted with 5 mL of sterile water, manually shaken until completely dissolved, and a sample was drawn using a syringe with a 32G needle. The sample was then extruded to test the smoothness of the process. The pushing process was divided into three levels: Level 1: Smooth, no blockage; Level 2: Can pass through the 32G needle, but there is resistance when pushing the syringe; Level 3: Complete blockage, the syringe cannot be pushed. The test results are shown below. Figure 7 Table in Chinese.
[0040] The results showed that no residue adhered to the needle during the reconstitution process in Examples 1-7. Except for Examples 3 and 5, the other examples passed smoothly through a 32G needle without any obstruction. Through reconstitution, sedimentation, and pushing tests, it was found that Examples 1, 6, and 7 had shorter reconstitution times, slower sedimentation rates, and could pass smoothly through a 32G needle without obstruction, making them more convenient for clinical use. Therefore, Examples 1, 6, and 7 were preferred for biological performance testing.
[0041] Experiment Example 4 The safety and collagen regeneration stimulation capabilities of Examples 1, 6, and 7 were tested. The specific experimental methods are as follows: Human dermal fibroblasts in the logarithmic growth phase (HDF) were harvested at a concentration of 5 × 10⁻⁶ cells / cells. 3 / hole connected to a 96-well plate, with 2×10 5 Cells were inoculated into 6-well plates and cultured for 24 hours. Cells were then divided into a blank control group, Example 1 group, Example 6 group, and Example 7 group. Each group was treated with an equal volume of sterile water and the reconstituted sample from the Example 7 group. After 48 hours of further culture, cell viability in 96-well plates was assessed using a CCK-8 assay. Cells from 6-well plates were collected, centrifuged at 3000 rpm for 15 minutes, and the supernatant was used to determine the total collagen content using a hydroxyproline assay kit. Specific test results are shown below. Figure 8 Table in Chinese.
[0042] The results showed that after co-culturing the samples from Examples 1, 6, and 7 with cells for 48 hours, cell viability was not significantly affected, and the samples exhibited a certain degree of cell proliferation, indicating that the samples in each group were non-cytotoxic and had good biocompatibility. Quantitative detection of collagen showed that all samples had a certain degree of effect in promoting collagen regeneration. Among them, Example 1 showed the most significant effect in promoting collagen secretion by cells.
[0043] This invention provides an injectable composite lyophilized powder with good biocompatibility and safety. The lyophilized powder has a short reconstitution time, slow sedimentation rate, and good needle penetration, making it convenient for injection. It also provides both immediate and long-term effects, offering immediate hydration and deep moisturization, while also stimulating collagen regeneration and improving facial condition. It has promising application prospects.
[0044] Although embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details and illustrations shown and described herein.
Claims
1. A compound lyophilized powder for injection, characterized in that, It includes poly-L-lactic acid microspheres, sodium hyaluronate, and mannitol.
2. The injectable compound lyophilized powder as described in claim 1, characterized in that, The poly-L-lactic acid microspheres, sodium hyaluronate, and mannitol are in a mass ratio of (3-4):(0.5-1.5):(2-4), with the remainder being phosphate.
3. The injectable compound lyophilized powder as described in claim 1 or 2, characterized in that, The molecular weight of the sodium hyaluronate is 200-800 kDa.
4. The injectable compound lyophilized powder as described in claim 1 or 2, characterized in that, The poly-L-lactic acid microspheres have a particle size of 20-40 μm.
5. The composite lyophilized powder for injection as described in claim 1, characterized in that, It also contains phosphates, which are one or both of sodium dihydrogen phosphate and disodium hydrogen phosphate.
6. A method for preparing a composite lyophilized powder for injection, characterized in that, Includes the following steps: S1: Preparation of poly-L-lactic acid microspheres; S2: Preparation of excipient solution: Add sodium hyaluronate, mannitol, and phosphate to water for injection and stir to dissolve; S3: Add the prepared poly-L-lactic acid microspheres to the excipient solution and stir to mix well; S4: Freeze-dry to obtain a composite lyophilized powder for injection.
7. The method for preparing a composite lyophilized powder for injection as described in claim 6, characterized in that, In step S1, the preparation of poly-L-lactic acid microspheres includes: S101: Polyvinyl alcohol is mixed and dissolved with water for injection to obtain an aqueous phase; dichloromethane and poly-L-lactic acid are mixed and dissolved to obtain an oil phase; S102: The oil phase and aqueous phase solutions are filtered through a 0.22um filter membrane and connected to the designated channels of the microfluidic chip. The flow rate of the two phases is controlled by the negative pressure of the air pump, so that stable microspheres with a particle size of 20-40um can be continuously formed. S103: The obtained microspheres are cured and the organic solvent is removed by evaporation. The polyvinyl alcohol is washed away by repeated water washing. After collection and drying, poly-L-lactic acid microspheres are obtained.
8. The method for preparing a composite lyophilized powder for injection as described in claim 6, characterized in that, The phosphates include sodium dihydrogen phosphate and disodium hydrogen phosphate.
9. The method for preparing a composite lyophilized powder for injection as described in claim 6, characterized in that, In step S4, the freeze-drying step includes: S401: Pre-freeze the solution obtained in step S3 at -45°C for 2-3 hours; S402: Single drying: Maintain at -20℃ to -25℃ for 48 to 52 hours; S403: Secondary drying: Maintain at 10℃~30℃ for 10~15 hours to complete.
